Field availability and avoidance of imidacloprid-treated soybean seeds and cotyledons by birds - Addy Orduna, Laura (2023)
Treated seeds and their cotyledons can present a toxicological risk to seed-eating birds. To assess whether avoidance behavior limits exposure and consequently the risk to birds, three fields were sown with soybeans. Half of the surface of each field was sown with seeds treated with 42 g /100 kg seed of insecticide imidacloprid (T plot, treated) and the other half with seeds without imidacloprid (C plot, control). Unburied seeds were surveyed in C and T plots at 12 h and 48 h post-sowing. Damaged seedlings was surveyed in C and T plots at 12 days post-sowing. Abundance and richness of birds was surveyed at the field level (without distinguishing between C and T plots) before, during, and after sowing, and 12 days post-sowing. Seed density was higher in the headlands of the T plots than in the C plots, but did not differ between 12 and 48 h. The damage on cotyledons of seedlings was 15.4% higher in C plots than in T plots. The abundance and richness per hectare of birds that eat seeds and cotyledons were lower after sowing, indicating a deterrent effect of sowing imidacloprid-treated seeds on birds. Although the variation in seed density over time does not allow solid conclusions to be drawn about the avoidance of seeds treated by birds, the seedling results suggest an aversive effect of imidacloprid-treated soybeans on birds. The dominant species was the eared dove (Zenaida auriculata), whose risk of acute poisoning by imidacloprid in soybean seeds and cotyledons was low, according to its toxicity exposure ratio (TER), its foraged area of concern, and its foraged time of concern.